A bifurcated molecular pentad capable of sequential electronic energy transfer and intramolecular charge transfer1. Issue 39 (21st October 2015) - Harriman, Anthony; Stachelek, Patrycja; Sutter, Alexandra; Ziessel, Raymond
<x xml:space="preserve">Abstract</x> The title compound absorbs strongly over much of the solar range and undergoes a variety of photophysical events under illumination.